Niche Differentiation and Prey Selectivity among Common Bottlenose Dolphins (Tursiops truncatus) Sighted in St. George Sound, Gulf of Mexico - Wilson, Rachel M.; Tyson, Reny B.; Nelson, James A.; Balmer, Brian C.; Chanton, Jeffrey P.; Nowacek, Douglas P. (Frontiers in Marine Science, 2017)
Two groups of common bottlenose dolphins (Tursiops truncatus) have been identified within St. George Sound, Florida, USA: high site-fidelity individuals (HSF) which are individuals sighted multiple times in the region (i.e., ≥ 2 months, ≥ 2 seasons, and ≥ 2 years), and low site-fidelity individuals (LSF), which are individuals sighted fewer than 2 months, in 2 different seasons among 2 different years. Our goal was to determine whether differences in foraging behaviors were correlated with differences in sighting frequency and overall usage of St. George Sound by the two groups. We used carbon, nitrogen, and sulfur stable isotopes and niche hypervolume metrics to model the foodweb of St. George Sound. The mixing model indicated that croaker, mojarra, pigfish, pinfish, and silverperch were the most important prey items for dolphins. The hypervolume metrics demonstrate niche partitioning between HSFs and LSFs, with the HSFs relying more heavily on pinfish, pigfish, and mojarra, while the LSFs relied more on silverperch. Plankton, benthic diatoms, seagrass, and epiphytes all contributed to secondary production within St. George Sound. This diversity of source utilization by seagrass-associated consumers supported by a high rate of total production likely sustains high secondary productivity despite the potential for competition in this system. Zooplankton was the most important basal source to the system, followed by seagrass and benthic primary production (as indicated by a sanddollar proxy). The reliance of dolphins on seagrass-dependent prey indicates that alteration of seagrass habitat would significantly impact the dolphin community foraging in St. George Sound and suggests that preservation of seagrass habitat is an important component of an effective management strategy for dolphin populations in the region.